Evaluación de la prevención y atención de derrames en proyectos lineales del sector de hidrocarburos: caso oleoductos. (2020)
In this monograph, environmental risk management was studied and evaluated in a section of the Bicentenario pipeline, taking into account the National Contingency Plan in the Araguaney-Banadía section. The crude transport mechanisms, the geographical and hydrological area of ​​the section located in Yopal, the environmental aspects, the causes and consequences related to possible events or incidents, the risks existing in the pumping station, the section of the pipeline and community. The risk assessment was exemplified by applying the Colombian Technical Guide 45 in the event of an explosion due to a spill caused by corrosion and subsequent pipeline rupture and the National Contingency Plan. In addition, environmental risk treatment options based on Technical Guide 104 and the importance of risk communication were described. A summary of the environmental risks in Colombia was presented for each of the oil pipelines, highlighting the importance of carrying out comprehensive management in a country where terrorist attacks and sabotage to the industry complicate the development of a systematic plan for risk management.